AKOMODASI KOMUNIKASI DALAM INTERAKSI ANTARBUDAYA SUKU OCU DENGAN SUKU JAWA DI DESA PONGKAI SELATAN SIBERUANG KAMPAR - Kurniawati, Eka; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Indonesia is a country that has a very diverse culture. The intercultural interactions that occur among people of different cultures are not easy. This is because of differences such as language, tradition, customs, customs, moral values, ethics, religion, and so forth. Usually people living in different cultural communities tend to adapt or accommodate their opposite cultures. In the process of communications accommodation, there are three common strategies in society when interacting. Namely the strategy of Convergence, Divergences and over-accomodation. This study aims to determine the forms of these strategies in the interaction between cultures Ocu tribe with the Java Tribe in the Village South Pongkai Siberuang Koto Kampar Hulu District Kampar regency.This research uses descriptive qualitative method with symbolic interaction approach and using observation data collection technique, interview and documentation. Technique of examination of data with triangulation technique. Allows researchers to recheck their findings by comparing them with different sources, methods or theories.The result of the research shows that Convergence strategy done by citizens of Ocu and Suku Jawa tribe is using the native language of the speaker while speaking with the original dialect of the culture of the other person. In the case of this language, the Javanese tribe more often converges the Ocu tribe. not paying attention to the distance at the moment of communication with the opponent. In terms of cultural values, the tribe Ocu follow the customs of the Javanese people in making an event like a feast and a wedding party. Divergensi strategy is to use a different language with the language of his opponent. avoiding touch among the opposite sex. Not trying to learn the language of the opponent. Divergences in terms of cultural values, when the Javanese choose to keep the Javanese tradition in every event held even though Pongkai is famous for its strict customs. Last Form of excessive accommodation that is When they joke and mock each other's language.